Contribution of Lecturer Characteristics in the Formation of Accounting Student Competency: A Study at Higher Education Institutions in Yogyakarta Special Region - Susanto, Heri; Saputri, Evieana Riesty; Wicaksono, Crescentiano Agung (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
Purpose : This study investigates the influence of lecturer competence on student competencies in the context of online learning, addressing a research gap concerning the role of lecturers in adapting to new educational technologies. Methodology: We collected data from vocational colleges in Yogyakarta (DIY) and Central Java through comprehensive observations and questionnaires. The gathered information was analyzed using regression analysis techniques to determine the relationship between lecturers' ICT understanding, their attitudes, and the resulting impact on student competence. Findings: Our findings reveal a positive correlation between lecturers' proficiency in ICT and their attitudes, significantly affecting student competencies. The results underscore the importance of technological literacy among lecturers, who must master various online learning tools. Additionally, the attitudes displayed by lecturers play a critical role in shaping student behavior and engagement in the learning process. Novelty : This study fills a significant research gap by highlighting the essential dimensions of lecturer competence in the realm of online learning. It emphasizes the need for lecturers to adapt to technological advancements and showcases the impact of their attitudes on student engagement and respect, which are crucial for effective learning in a technology-driven era. Keywords: behavioral accounting, lecturer competence, online learning